Style kierowania w organizacjach opierających swój rozwój na współpracy z klientami - Piwoni-Krzeszowska, Estera (Management styles in organizations growing thanks to co-operation with customers, 2005)
Shaping co-operation with customers consists in initiating and fostering a relationship. A variety of episodes (situations) occur in the course of these processes. Dependent on whether these are routine or extraordinary, the processes require different management styles. Their adaptation to the existing conditions determines the development of co-operation and at the same time substantially affects the business success of organizations operating in a dynamic environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 514-521